Heterojunction vanadium oxide / three-dimensional graphite paper aqueous magnesium ion battery electrode material and preparation method thereof
The three-dimensional graphite paper current collector was prepared through electrochemical peeling and electrodeposition technology and the sea urchin-like nanostructure of V2O5@VO2·xH2O composite was solved, which solved the problems of low conductivity of vanadium oxide materials in aqueous magnesium ion batteries and slow diffusion of magnesium ions, and achieved high-performance electrochemical magnesium storage effect.
Patent Information
- Application Number
- CN202411685575.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-23
AI Technical Summary
The application of vanadium oxide materials in aqueous magnesium ion batteries is limited by their low conductivity and slow diffusion of magnesium ions.
Electrochemical peeling technology is used to prepare three-dimensional graphite paper current collectors, and then heterojunction vanadium oxide material is prepared on its surface by electrodeposition method to form a sea urchin-like nanostructure of V2O5@VO2·xH2O composite.
The rapid preparation of vanadium oxide electrode materials has been achieved, the conductivity and ion diffusion kinetics have been improved, and the electrochemical magnesium storage performance of aqueous magnesium ion batteries has been significantly improved.
Smart Images

Figure CN119627055A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based energy storage materials, and in particular relates to a method for preparing a heterojunction VO2·xH2O@V2O5 magnesium storage electrode. Background Art
[0002] Aqueous magnesium ion batteries (AMIBs) play an important role in the field of large-scale energy storage due to their low cost, long cycle life and high safety. AMIBs are mainly composed of electrode materials, separators, aqueous electrolytes, etc. Each part has a great influence on AMIBs, among which the electrode materials play a decisive role in the performance of AMIBs. Vanadium oxide is a common transition metal oxide. It has the advantages of high theoretical specific capacity, structural diversity and easy preparation, making it a very promising electrode material for AMIBs. However, the low conductivity and strong Mg-O interaction severely limit the performance of vanadium oxide materials, resulting in less application in AMIBs. Therefore, it is of great significance to develop vanadium oxide electrodes with excellent conductivity and ion diffusion kinetics.
[0003] At present, the main methods to improve the performance of vanadium oxide are material nano-sizing, heteroatom doping and carbon coating modification. For example, Fu et al. reported a hydrothermal synthesis of hydrated Ca 2+ AMIBs cathode materials doped with V2O5 achieve better rate performance by regulating the electrolyte (Energy Storage Materials 66 (2024) 103212). Xu et al. synthesized Mg by hydrothermal method 2+ Mg co-doped with H2O 0.3 V2O5·1.1H2O AMIBs positive electrode material achieves good cycle performance (Chem 5(2019) 1194-1209). Although these methods have improved the performance of vanadium oxide to a certain extent, they have high equipment requirements and are time-consuming. Therefore, it is necessary to develop a simple and fast preparation technology for vanadium oxide electrode materials to achieve high-performance AMIBs. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned preparation technology and provide a method for rapidly preparing a vanadium oxide magnesium storage heterojunction electrode with a sea urchin-like nanostructure, so as to solve the problems of low conductivity of vanadium oxide and slow diffusion of magnesium ions. The method is based on electrochemical technology to prepare a three-dimensional graphite paper current collector, and then electrodeposit the vanadium oxide heterojunction nanomaterial on the surface of the three-dimensional graphite paper current collector. The method comprises the following steps:
[0005] 1. Preparation of 3D graphite paper current collector
[0006] In a three-electrode electrolytic cell system, graphite paper is used as the working electrode, Pt sheet is used as the counter electrode, and saturated calomel electrode is used as the reference electrode. The electrochemical stripping is divided into three steps: (1) cyclic voltammetry initial stripping in a low-concentration alkaline solution; (2) constant voltage secondary stripping in a salt solution; (3) cyclic voltammetry scanning in a salt solution to restore the conductivity and surface wettability of graphite paper.
[0007] 2. Preparation of heterojunction vanadium oxide materials
[0008] In a three-electrode system, the three-dimensional graphite paper prepared in 1 is used as the working electrode, the unpeeled graphite paper is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode to electrodeposit the vanadium oxide heterojunction material. The electrolyte for electrodeposition is a mixed solution of sulfate and acetate, and the electrodeposition is carried out by cyclic voltammetry. After the reaction is completed, the working electrode is taken out, washed and dried to obtain the heterojunction vanadium oxide electrode material.
[0009] Wherein, the alkaline solution in (1) is NaOH or KOH with a solubility of 0.3-0.6 M; the scanning voltage range of the cyclic voltammetry is 0.5-1.7 V, the scanning rate is 10-30 mV / s, and the number of cycles is 5-10.
[0010] The salt solution in (2) of 1 is NaNO3 or KNO3, with a solubility of 1-2.5 M, a voltage of 1.8 V, and a deposition time of 3-10 min.
[0011] The salt solution in (3) of 1 is KNO3 or LiNO3 with a concentration of 1~2.5 M. The surface of the working electrode needs to be cleaned with deionized water before operation.
[0012] The voltage range of the cyclic voltammetry in 1 (3) is -1 to 1 V, the scan rate is 10 to 30 mV / s, and the number of scans is 20 to 30.
[0013] The sulfate in 2 is VOSO4, with a purity greater than 99%, and a concentration of 0.1-0.5 M, and the acetate is CH3COONH4, with a concentration of 0.1-0.5 M. The volume ratio of VOSO4 to CH3COONH4 is 1: 1-2.
[0014] The voltage range of the cyclic voltammetry method used in the electrodeposition of heterojunction vanadium oxide in the second embodiment is -1 to 1.5 V, the scanning rate is 20 to 30 mV / s, and the number of scanning circles is 10 to 30 circles.
[0015] The washing solvents in the above two are ethanol and deionized water, and the drying method is vacuum freeze drying.
[0016] The composition of the heterojunction vanadium oxide in the second embodiment is a composite of V2O5 and VO2·xH2O, and its morphology is a three-dimensional sea urchin-like structure self-assembled by nanobelts, and the width of the nanobelts is 8-30 nm.
[0017] The basic principle of the present invention is
[0018] Electrochemical exfoliation of graphite paper is an efficient exfoliation method. Its principle is to embed electrolyte ions between graphite layers, and use the electrochemical oxidation process to introduce oxygen-containing functional groups and bubbles generated by water decomposition to weaken the van der Waals forces between graphite layers, thereby exfoliating the graphite layers. The degree of exfoliation is controlled by adjusting the electrolyte concentration and the exfoliation time, so that a large number of graphite sheets or graphene are rolled up from the surface of the graphite block, and then the conductivity of the rolled-up oxidized graphite sheets is restored through the electrochemical reduction process to obtain a three-dimensional graphite paper current collector.
[0019] Electrodeposition is a common method for preparing heterojunction materials. By controlling the conditions of electrodeposition (voltage window, current density and reaction time), the manufacture and adjustment of heterojunctions can be achieved, which has the advantages of low cost and high efficiency. In the present invention, the preparation of heterojunction vanadium oxide adopts cyclic voltammetry. In this method, the deposition potential needs to be above the starting potential of the electrochemical reaction to start the deposition reaction, and the deposition rate gradually increases with the increase of the deposition potential. Therefore, the crystal phase structure of the prepared heterojunction material is relatively uniform. Due to the large positive voltage range, most of the deposited vanadium oxide is high-valent V2O5. In addition, in the rapid oxidation / reduction process, the crystal form of the high-valent V2O5 surface part changes rapidly to generate low-valent VO2. Since the electrolyte is an aqueous solution, it is easy to embed water molecules in the vanadium oxide structure.
[0020] Compared with the prior art, the present invention has the following advantages
[0021] (1) The present invention uses electrochemical stripping technology and electrodeposition technology to prepare heterojunction composite materials. The equipment is simple, the operation is convenient, and harsh preparation conditions are avoided. Most importantly, the preparation time is short.
[0022] (2) The three-dimensional graphite paper current collector as a substrate has a large specific surface area, high space utilization, and high conductivity.
[0023] (3) Vanadium oxide is grown on the surface of three-dimensional graphite paper using the COV force of chemical bonds, ensuring the stability of the electrode material structure.
[0024] (4) The heterojunction vanadium oxide consists of a layered structure of V2O5 and a tunnel structure of VO2·xH2O. This structure provides multiple ion diffusion paths and has high ion diffusion kinetics.
[0025] (5) The V2O5@VO2·xH2O composite heterojunction material obtained in the present invention has excellent electrochemical magnesium storage performance and can be further applied to the field of energy materials such as zinc, calcium and aluminum storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope photo of the three-dimensional graphite paper current collector material prepared in Example 1;
[0027] Figure 2 This is a scanning electron microscope photograph of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 1;
[0028] Figure 3 This is a transmission electron microscope photograph of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 1;
[0029] Figure 4 This is an X-ray diffraction image of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 1;
[0030] Figure 5 Performance diagram of the V2O5@VO2·xH2O composite heterojunction electrode prepared in Example 1;
[0031] Figure 6 This is a scanning electron microscope photo of the three-dimensional graphite paper current collector material prepared in Example 2;
[0032] Figure 7 This is a scanning electron microscope photograph of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 2;
[0033] Figure 8 This is a transmission electron microscope photograph of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 2;
[0034] Fig. 9 Performance diagram of the V2O5@VO2·xH2O composite heterojunction electrode prepared in Example 2;
[0035] Fig.10 This is a scanning electron microscope photo of the three-dimensional graphite paper current collector material prepared in Example 3;
[0036] Fig.11 This is a scanning electron microscope photograph of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 3;
[0037] Fig.12 This is a transmission electron microscope photograph of the V2O5@VO2·xH2O composite heterojunction material prepared in Example 3;
[0038] Fig.13This is a performance diagram of the V2O5@VO2·xH2O composite heterojunction electrode prepared in Example 3. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with embodiments.
[0040] (1) A scanning electron microscope SU8010 from Hitachi, Japan, was used to observe the morphology and structural characteristics of the samples.
[0041] (2) A transmission electron microscope (TEM) JEM2100F from Japan Electron Corporation was used to observe the internal microstructure of the samples.
[0042] (3) The X-ray diffractometer PANalytical X'Pert PRO from PANalytical of the Netherlands was used to observe the crystal composition of the samples.
[0043] (4) The electrochemical test was carried out using a three-electrode system, in which the prepared electrode was the working electrode, the saturated calomel electrode was the reference electrode, the Pt sheet was the counter electrode, and 4 M MgCl2 was the electrolyte. The electrochemical test window was -0.3~1.0 V.
[0044] The chemical reagents used in the examples of the present invention are provided by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0045] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Any technical solutions that do not deviate from the spirit and scope of the present invention should be included in the scope of protection of the present invention.
[0046] Embodiment 1
[0047] 1. Preparation of three-dimensional graphite paper current collector:
[0048] In a three-electrode electrolytic cell system, graphite paper was used as the working electrode, Pt sheet as the counter electrode, and saturated calomel electrode as the reference electrode. The electrochemical stripping was divided into three steps: (1) In the three-electrode system, 0.5 M 30 mL KOH was used as the electrolyte for preliminary cyclic voltammetry stripping. The parameters were set as the scanning voltage range of 0.5~1.7 V, the scanning rate of 20 mV / s, and the number of scanning cycles of 10. (2) In the three-electrode system, 1 M 30 mL KNO3 was used as the electrolyte for constant voltage secondary stripping. The parameters were set as the voltage value of 1.8 V and the reaction time of 10 min. (3) To restore the conductivity and surface wettability of graphite paper, the working electrode was briefly cleaned and placed in 1 M 30 mL KNO3 for cyclic voltammetry treatment. The parameters were set as the scanning voltage range of -1~1 V, the scanning rate of 20 mV / s, and the number of scanning cycles of 20. After the reaction is completed, the working electrode is removed, washed with deionized water, and then freeze-dried to obtain the final three-dimensional graphite paper current collector. The scanning electron microscope image is as follows: Figure 1 shown.
[0049] 2. Preparation of heterojunction vanadium oxide materials
[0050] In a three-electrode system, the three-dimensional graphite paper prepared in 1 above was used as the working electrode, the unpeeled graphite paper was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode to electrodeposit a vanadium oxide heterojunction. The electrolyte for electrodeposition was 30 mL of a mixed solution of VOSO4 and CH3COONH4 with a volume ratio of 1:1, wherein VOSO4 provided a vanadium source with a concentration of 0.5 M, and CH3COONH4 was a buffer solution with a concentration of 0.5 M. The parameters of the cyclic voltammetry were set to a voltage range of -1~1.5 V, a scan rate of 20 mV / s, and a scan number of 20 circles. After the reaction was completed, the working electrode was taken out, washed three times with deionized water and ethanol respectively, and freeze-dried to obtain a heterojunction vanadium oxide (V2O5@VO2·xH2O) electrode material. Its scanning electron microscope image is shown in the figure below. Figure 2 As shown, its morphology is a three-dimensional sea urchin-like structure self-assembled by nanobelts; the transmission electron microscopy image is shown in Figure 3 As shown, the width of the nanobelt is 8~20 nm; the X-ray diffraction pattern is shown Figure 4 As shown, it indicates that it is a mixed phase heterojunction composition.
[0051] The performance of the electrode prepared under these conditions was tested in a three-electrode system. The results showed that the V2O5@VO2·xH2O composite heterojunction material had a -1 The magnesium storage capacity is 510 mAh g -1 , at 5 A g -1 The specific capacity of magnesium storage is 195.5 mAh g -1 ,like Figure 5shown.
[0052] Embodiment 2
[0053] 1. Preparation of three-dimensional graphite paper current collector:
[0054] In a three-electrode electrolytic cell system, graphite paper was used as the working electrode, Pt sheet as the counter electrode, and saturated calomel electrode as the reference electrode. The electrochemical stripping was divided into three steps: (1) In the three-electrode system, 0.5 M 30 mL KOH was used as the electrolyte for preliminary cyclic voltammetry stripping. The parameters were set as the scanning voltage range of 0.5~1.7 V, the scanning rate of 20 mV / s, and the number of scanning cycles of 10. (2) In the three-electrode system, 1 M 30 mL KNO3 was used as the electrolyte for constant voltage secondary stripping. The parameters were set as the voltage value of 1.8 V and the reaction time of 8 min. (3) To restore the conductivity and surface wettability of graphite paper, the working electrode was briefly cleaned and placed in 2.5 M 30 mL LiNO3 for cyclic voltammetry treatment. The parameters were set as the scanning voltage range of -1~1 V, the scanning rate of 20 mV / s, and the number of scanning cycles of 30. After the reaction is completed, the working electrode is removed, washed with deionized water, and then freeze-dried to obtain the final three-dimensional graphite paper current collector. The scanning electron microscope image is as follows: Figure 6 As shown, it can be seen that after a long period of peeling, the peeling degree of the graphite paper surface increases and local small fragments are generated.
[0055] 2. Preparation of heterojunction vanadium oxide materials
[0056] In a three-electrode system, the three-dimensional graphite paper prepared in 1 above was used as the working electrode, the unpeeled graphite paper was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode to electrodeposit a vanadium oxide heterojunction. The electrolyte for electrodeposition was 30 mL of a mixed solution of VOSO4 and CH3COONH4 with a volume ratio of 1:2, wherein VOSO4 provided a vanadium source with a concentration of 0.5 M, and CH3COONH4 was a buffer solution with a concentration of 0.5 M. The parameters of the cyclic voltammetry were set to a voltage range of -1~1.5 V, a scan rate of 20 mV / s, and a scan number of 30 circles. After the reaction was completed, the working electrode was taken out, washed three times with deionized water and ethanol respectively, and freeze-dried to obtain a heterojunction vanadium oxide (V2O5@VO2·xH2O) electrode material. Its scanning electron microscope image is shown in the figure below. Figure 7 As shown, its morphology is a three-dimensional sea urchin-like structure self-assembled by dense nanobelts; the transmission electron microscopy image is shown in Figure 8 As shown, it shows that its nanoribbons have an interwoven sea urchin-like structure and the width of the nanoribbons is 8~30 nm.
[0057] The performance of the electrode prepared under these conditions was tested in a three-electrode system. The results showed that the V2O5@VO2·xH2O composite heterojunction material had a -1 The magnesium storage capacity is 450 mAh g -1 , at 5 A g -1 The magnesium storage capacity is 190 mAh g -1 ,like Fig. 9 shown.
[0058] Embodiment 3
[0059] 1. Preparation of three-dimensional graphite paper current collector:
[0060] In a three-electrode electrolytic cell system, graphite paper was used as the working electrode, Pt sheet as the counter electrode, and saturated calomel electrode as the reference electrode. The electrochemical stripping was divided into three steps: (1) In the three-electrode system, 0.5 M 30 mL KOH was used as the electrolyte for preliminary cyclic voltammetry stripping. The parameters were set as the scanning voltage range of 0.5~1.7 V, the scanning rate of 20 mV / s, and the number of scanning cycles of 5. (2) In the three-electrode system, 2.5 M 30 mL KNO3 was used as the electrolyte for constant voltage secondary stripping. The parameters were set as the voltage value of 1.8 V and the reaction time of 3 min. (3) To restore the conductivity and surface wettability of graphite paper, the working electrode was briefly cleaned and placed in 2.5 M 30 mL KNO3 for cyclic voltammetry treatment. The parameters were set as the scanning voltage range of -1~1 V, the scanning rate of 20 mV / s, and the number of scanning cycles of 20. After the reaction is completed, the working electrode is removed, washed with deionized water, and then freeze-dried to obtain the final three-dimensional graphite paper current collector. The scanning electron microscope image is as follows: Fig.10 As shown, it can be seen that due to the short peeling time, the surface of the graphite paper is slightly peeled off and a good three-dimensional structure cannot be produced.
[0061] 2. Preparation of heterojunction vanadium oxide materials
[0062] In a three-electrode system, the three-dimensional graphite paper prepared in 1 above was used as the working electrode, the unpeeled graphite paper was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode to electrodeposit a vanadium oxide heterojunction. The electrolyte for electrodeposition was 30 mL of a mixed solution of VOSO4 and CH3COONH4 with a volume ratio of 1:2, wherein VOSO4 provided a vanadium source with a concentration of 0.2 M, and CH3COONH4 was a buffer solution with a concentration of 0.2 M. The parameters of the cyclic voltammetry were set to a voltage range of -1~1.5 V, a scan rate of 20 mV / s, and 10 scans. After the reaction was completed, the working electrode was taken out, washed three times with deionized water and ethanol respectively, and freeze-dried to obtain a heterojunction vanadium oxide (V2O5@VO2·xH2O) electrode material. The scanning electron microscope image is shown in the figure below. Fig.11 As shown, its morphology is a nanobelt structure. Due to the low concentration of electrolyte and short deposition time, the nanobelts are not assembled into a three-dimensional structure; the transmission electron microscopy image is shown in Fig.12 As shown, it indicates that the width of its nanoribbon is 8~20 nm.
[0063] The performance of the electrode prepared under these conditions was tested in a three-electrode system. The results showed that the V2O5@VO2·xH2O composite heterojunction material had a -1 The magnesium storage capacity is 300 mAh g -1 , at 5 A g -1 The magnesium storage capacity is 120 mAh g -1 ,like Fig.13 shown.
[0064] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a heterojunction VO2·xH2O@V2O5 magnesium storage electrode, characterized in that: The method for preparing comprises the following steps: (1) Electrochemical preparation of three-dimensional graphite paper current collector: In the three-electrode system, graphite paper is used as the working electrode, Pt sheet is used as the counter electrode, and saturated calomel electrode is used as the reference electrode. The electrochemical stripping is divided into three steps: 1) preliminary stripping by cyclic voltammetry in a low-concentration alkaline solution; 2) secondary stripping by constant voltage in a salt solution; 3) cyclic voltammetry scanning in a salt solution to restore the conductivity of graphite paper; (2) Preparation of heterojunction vanadium oxide material: In a three-electrode system, the three-dimensional graphite paper prepared in (1) is used as the working electrode, the unpeeled graphite paper is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode to electrodeposit the vanadium oxide heterojunction material; the electrolyte for electrodeposition is a mixed solution of sulfate and acetate, and the electrodeposition is carried out by cyclic voltammetry; after the reaction is completed, the working electrode is taken out, washed and dried to obtain the heterojunction vanadium oxide electrode material.
2. The preparation method according to claim 1, characterized in that: The alkaline solution in step (1) is NaOH or KOH with a solubility of 0.3~0.6 M, the scanning voltage range of the cyclic voltammetry is 0.5~1.7 V, the scanning rate is 10~30 mV / s, and the number of cycles is 5~10; the salt solution is NaNO3 or KNO3 with a solubility of 1~2.5 M, the constant voltage stripping voltage is 1.8 V, and the deposition time is 3-10 min; the salt solution for restoring the conductivity of the graphite paper is KNO3 or LiNO3 with a concentration of 1~2.5 M, the voltage range of the cyclic voltammetry is -1~1 V, the scanning rate is 10~30 mV / s, and the number of scans is 20~30.
3. The preparation method according to claim 1, characterized in that: The sulfate is VOSO4, the acetate is CH3COONH4, the volume ratio of VOSO4 to CH3COONH4 is 1: 1~2; the voltage range of the cyclic voltammetry is -1~1.5 V, the scan rate is 20~30 mV / s, and the number of scans is 10~30 circles.
4. The heterojunction VO2·xH2O@V2O5 electrode prepared according to any one of claims 1 to 3, characterized in that: The composition of the VO2·xH2O@V2O5 is a composite of V2O5 and VO2·xH2O, and the morphology is that nanobelts are self-assembled into a three-dimensional sea urchin-like structure, wherein the width of the nanobelts is 8-30 nm.
Citation Information
Patent Citations
Flexible self-supporting vanadium-based heterojunction / graphene composite material as well as preparation method and application thereof
CN112133895A
Vanadium oxide electrode material with nanorod structure, and preparation method and application thereof
CN113223865A
Preparation method of vanadium-based two-dimensional heterojunction material and application of vanadium-based two-dimensional heterojunction material as positive electrode material in zinc ion battery
CN114628667A